Feeling Everyday IR: Embodied, affective, militarising movement as choreography of war. (June 2019) - Åhäll, Linda
This article explores affective, embodied encounters between military and civilian bodies in the everyday as choreography of war. It argues that by paying attention to the intersecting political sphere of bodies, affect and movement – through the metaphor of 'dance' – we are not only able to understand how security operates as a logic reproducing the militarisation of the everyday, but also able to identify a representational gap, an aesthetic politics, potentially useful for resistance to such practices normalising war in the everyday. It draws on two British examples of where military moves disrupt civilian spaces in the everyday: an arts project commemorating the Battle of the Somme, and a football game taking place during Remembrance week. Through embodied choreographies of war in the everyday, dance is used as a metaphor to understand militarisation as an example of feeling Everyday IR. Thus, dance is useful to 'see' the politics of Everyday IR, but also to understand, to feel and possibly to resist the politics of normalisation of war in the everyday. This is one example of how feeling Everyday IR offers alternative openings into political puzzles of security logics informing war as practice.